3D Oxygen‐Enhanced MRI at 3T MR System: Comparison With Thin‐Section CT of Quantitative Capability for Pulmonary Functional Loss Assessment and Clinical Stage Classification of COPD in Smokers. Issue 4 (17th November 2020) - Ohno, Yoshiharu; Yui, Masao; Yoshikawa, Takeshi; Seki, Shinichiro; Takenaka, Daisuke; Kassai, Yoshimori; Hattori, Hidekazu; Murayama, Kazuhiro; Toyama, Hiroshi
Abstract : Background: Oxygen (O2 )‐enhanced MRI is mainly performed by a 2D sequence using 1.5T MR systems but trying to be obtained by a 3D sequence using a 3T MR system. Purpose: To compare the capability of 3D O2 ‐enhanced MRI and that of thin‐section computed tomography (CT) for pulmonary functional loss assessment and clinical stage classification of chronic obstructive pulmonary disease (COPD) in smokers. Study Type: Prospective study. Population: Fifty six smokers were included. Field Strength/ Sequence: 3T, 3D O2 ‐enhanced MRIs were performed with a 3D T1 ‐weighted fast field echo pulse sequence using the multiple flip angles. Assessments: Smokers were classified into four stages ("Without COPD, " "Mild COPD, " "Moderate COPD, " "Severe or very severe COPD"). Maps of regional changes in T1 values were generated from O2 ‐enhanced MR data. Regions of interest (ROIs) were then placed over the lung on all slices and averaged to determine mean T1 value change (ΔT1 ). Quantitative CT used the percentage of low attenuation areas within the entire lung (LAA%). Statistical Tests: ΔT1 and LAA% were correlated with pulmonary functional parameters, and compared for four stages using Tukey's Honestly Significant Difference test. Discrimination analyses were performed and McNemar's test was used for a comparison of the accuracy of the indexes. Results: There were significantly higher correlations between ΔT1 and pulmonary functional parameters (–0.83 ≤ r ≤ –0.71, P < 0.05) than between LAA% and the same pulmonary functional parameters (–0.76 ≤ r ≤ –0.69, P < 0.05). ΔT1 and LAA% of the "Mild COPD" and "Moderate COPD" groups were significantly different from those of the "Severe or Very Severe COPD" group ( P < 0.05). Discriminatory accuracy of ΔT1 (62.5%) and ΔT1 with LAA% (67.9%) was significantly greater than that of LAA% (48.2%, P < 0.05). Data Conclusion: Compared with thin‐section CT, 3D O2 ‐enhanced MRI has a similar capability for pulmonary functional assessment but better potential for clinical stage classification in smokers. Level of Evidence: 2 Technical Efficacy Stage: 1